BRIGHT LIFE AND CREATION OF SHUKUR KOLMIRZAYEV (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article provides information about Shukur Kholmirzayev's life and work, his contribution to Uzbek literature, his characters in his works and stories, and his role today .